A avaliação do desenvolvimento de déficit cognitivo em pacientes recuperados da COVID-19 - KATO, Beatriz De Sousa (2023)
The development of postCovid19 Cognitive Deficit infection and the pathogenic mechanisms involved in the pathophysiology of this, are still uncertain, but are probably multifactorial, but likely affect the neurotrophic effect of SARSCoV2. For a better understanding of this pathophysiology, studies are needed that better characterize the clinical profile of these patients, thus establishing the possible risk factors involved in this association. The objective of this study is to evaluate the development of cognitive deficits in people who had COVID19 infection and to characterize the clinical profile of this population. Cognitive assessment was performed using the Mini Mental State Examination (MMSE). Laboratory evaluation and collection of clinical epidemiological data, including application of the criteria for Metabolic Syndrome (MS) were also performed. The study included 112 patients and were subdivided into a case group (change in MMSE) and control (no change in MMSE). The study found a high prevalence of patients with postCovid19 cognitive impairment [n=46 (41%)]. Age was compared and there was a statistical difference between the groups (p<0.05), with the highest prevalence being between 51 and 60 years old [n=19 (41%)] in the case group. In the assessment of MS, a comparison was made between the case and control groups on the quantitative criteria in patients diagnosed with MS, using the Mann Whitney Test (p<0.05). Subsequently, Simple Logistic Regression was applied to this association, which also obtained a significant result (p<0.05). Multiple Logistic Regression was performed and the presence of any risk factor for Cognitive Deficit was not found independently. In addition, there was no relationship between the severity of Covid19 and the presence of olfactory symptoms with postCovid19 cognitive decline. We conclude that a set of risk factors for MS can influence the development of Cognitive Deficit, not showing an association of these criteria in isolation. Therefore, further studies are needed to investigate this association.